Modal mineralogy of CV3 chondrites by X-ray diffraction (PSD-XRD) - Howard, K.; Benedix, G.; Bland, Phil; Cressey, G. (Pergamon-Elsevier Science Ltd, 2010)
Using position sensitive detector X-ray diffraction (PSD-XRD) we determine a complete modal mineralogy for all phases present in abundances greater than 1 wt% in Vigarano, Efremovka, Mokoia, Grosnaja, Kaba and Allende. Reduced CV3 samples are comprised of (vol%): olivine (83–85%); enstatite (6.5–8.1%); anorthite (1.1–1.2%); magnetite (1.4–1.8%); sulphide (2.4–5.1%); Fe, Ni metal (2–2.2%). The oxidized samples are comprised of: olivine (76.3–83.9%); enstatite (4.8–7.8%); anorthite (1.1–1.7%); magnetite (0.3–6.1%); sulphide (2.9–8.1%); Fe, Ni metal (0.2–1.1%); Fe-oxide (0–2.7%) and phyllosilicate (1.9–4.2%). When our modal data is used to calculate a bulk chemistry that is compared to literature data a near 1:1 correlation is observed. PSD-XRD data indicates that olivine compositions may span almost the entire Fe–Mg solid solution series in all CV samples and that these contain a component (4–13%) of fine-grained olivine that is more Fe-rich (>Fa60) than is typically reported. Modal mineralogy shows that there are mineralogic differences between CV3 samples classified as oxidized and reduced but that these sub-classes are most clearly distinguished by the relative abundance of metal and Ni content of sulphide, rather than abundance of magnetite. The most significant difference in modal mineralogy observed is the relative absence of phyllosilicate in reduced CV that essentially escaped aqueous alteration.Fayalite, ferrous olivine and magnetite are typically considered secondary alteration products. The abundances of these minerals overlap in oxidized and reduced samples and correlate positively supporting common conditions of formation in a relatively oxidizing environment. The abundances of fayalite, ferrous olivine and magnetite show no relationship to petrographic type and if these abundances were used as a proxy for alteration, Allende would be the least altered CV – contrary to all previous data. The implication is that thermal metamorphism on the parent body was de-coupled from formation of Fe-rich secondary minerals. Low temperature fluid-assisted metamorphism can also not easily explain the origin of fayalite, ferrous olivine and magnetite, since the reduced CVs appear to be largely unaffected by this process. Parent body models require an anhydrous low-temperature mechanism of secondary alteration. The alternative is that these phases formed prior to accretion of the final CV parent body.